2012
DOI: 10.2135/cropsci2011.07.0395
|View full text |Cite
|
Sign up to set email alerts
|

Haploid Fertility in Temperate and Tropical Maize Germplasm

Abstract: Doubled haploid (DH) technology facilitates rapid development of homozygous inbred lines for hybrid breeding in maize {Zea mays L.). However, the required artificial chromosome duplication step, which commonly involves toxic and costly chemicals, represents a bottleneck. Exploiting the haploids' natural fertility may enable abolishment of artificial treatments and enhance efficiency of line development. We screened haploid populations derived from U.S. Corn Belt and tropical germplasm for the proportion of fer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
89
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(101 citation statements)
references
References 21 publications
(32 reference statements)
6
89
1
Order By: Relevance
“…Strong to moderate correlations were found between haploid and DH lines (Table 3). S4) were found in various genetic materials (Geiger and Schönleben, 2011;Kleiber et al, 2012). Preselection among untreated haploid plants directly sown in the field should therefore result in improved per se performance at the DH level.…”
Section: Discussionmentioning
confidence: 99%
“…Strong to moderate correlations were found between haploid and DH lines (Table 3). S4) were found in various genetic materials (Geiger and Schönleben, 2011;Kleiber et al, 2012). Preselection among untreated haploid plants directly sown in the field should therefore result in improved per se performance at the DH level.…”
Section: Discussionmentioning
confidence: 99%
“…Kleiber et al . () reported that the range of haploid fertility is 0%–20% in tropical and temperate maize germplasm. Wu et al .…”
Section: Genome Doublingmentioning
confidence: 99%
“…In doubling haploid germplasm, it has been shown that doubling rates of tropical landraces lag behind those of more elite tropical germplasm or Corn Belt materials (Kleiber et al. ). This is consistent with the low doubling rates observed in this experiment.…”
Section: Discussionmentioning
confidence: 99%